Juvenil, a natural immune booster affecting biological responses through modulation of gut microbiota composition - Boštíková, Vanda; Kubelková, Klára; Macela, Aleš (Vojenské zdravotnické listy, 2024)
Juvenil, a nontoxic extract of bovine blood, is registered as a dietary supplement having no side effects. It contains a broad spectrum of free amino acids, as well as small proteins and oligopeptides (molecular weights up to 10 kDa), various nucleotides, and small amounts of phospholipids. The complex of these exclusively natural components has been shown to support physiological responses of supplemented organisms.Juvenil has been studied for several decades using a wide range of both experimental and clinical studies. Analyses have shown that it acts directly neither on individual functional systems of the body nor on individual metabolic processes. Current findings indicate that modulatory effects of Juvenil occur through modulation of gut microbiota composition, which is associated with the modulation of microbiota-gut-brain axis signaling. In murine model that modulatory effect is reflected in the expression of an early activation c-Fos marker in specific parts of the brain.In this review we present a set of findings about Juvenil, which has a wide range of positive effects on the functional systems of organisms. These effects can be used to strenghten the resistance, immunity, and regeneration of human beings. According to its effects Juvenil can be classified as a psychobiotics.
Keywords: Probiotics; Dietary Supplements; aminokyseliny; Oligopeptides; Nucleotides; prebiotika; probiotika; imunitní systém; střevní mikroflóra; nukleotidy; Gastrointestinal Microbiome; osa mozek-střevo; potravní doplňky; Immune System; oligopeptidy; Brain-Gut Axis; Biological Products; Prebiotics; biologické přípravky; Amino Acids; lidé; Humans